Effect of airborne particle abrasion protocols on surface topography of Y-TZP ceramic - Queiroz, J. R C [UNESP]; Paulo, G. P. [UNESP]; Özcan, M.; Nogueira, L. [UNESP] (FapUNIFESP (SciELO), 2012)
This study aimed to evaluate Y-TZP surface after different airborne particle abrasion protocols. Seventy-six Y-TZP ceramic blocks (5×4×4) mm3 were sintered and polished. Specimens were randomly divided into 19 groups (n=4) according to control group and 3 factors: a) protocol duration (2 and 4 s); b) particle size (30 μm, alumina coated silica particle; 45 μm, alumina particle; and 145 μm, alumina particle) and; c) pressure (1.5, 2.5 and 4.5 bar). Airborne particle abrasion was performed following a strict protocol. For qualitative and quantitative results, topography surfaces were analyzed in a digital optical profilometer (Interference Microscopic), using different roughness parameters (Ra, Rq, Rz, X-crossing, Mr1, Mr2 and Sdr) and 3D images. Surface roughness also was analyzed following the primer and silane applications on Y-TZP surfaces. One-way ANOVA revealed that treatments (application period, particle size and pressure of particle blasting) provided significant difference for all roughness parameters. The Tukey test determined that the significant differences between groups were different among roughness parameters. In qualitative analysis, the bonding agent application reduced roughness, filing the valleys in the surface. The protocols performed in this study verified that application period, particle size and pressure influenced the topographic pattern and amplitude of roughness.
Keywords: Sandblast; Surface modification; Zirconia